Extension service requirements for the effective transfer of fisheries technologies - K. Arivukkarasu; N.V. Sujathkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was carried out in four fishing villages of Thoothukudi district of Tamil Nadu. A total of 120 fishermen was selected randomly from these villages and the data were collected through a well-structured pre-tested interview schedule with personal inquiry. The collected data were analysed and it was found that training, demonstration, on-the-spot guidance and mass media services were frequently required for the speedy dissemination of fisheries technologies when compared to other extension services.